Methodological approaches to constructing optimal learning trajectory for formation of communicative skills in different categories of learners - Garnyk, Liudmyla Petrivna; Snihurova, Irina Ivanivna (My University, 2023)
This article proposes to apply process approach to building optimal educational trajectory for formation of communicative skills, considering educational needs of various categories of learners, basing on comparative and historical review of methodological approaches to language learning. Authors emphasize importance of focusing on individual psychological and cognitive aspects (perception, memorization, reproduction) of information perception by different categories of language classes students.

У статті запропоновано застосувати процесний пдхід до побудови оптимальної навчальної траєкторії для формування комунікативних навичок із врахуванням освітніх потреб різних категорій здобувачів освітніх послуг на основі порівняльно-історичного огляду методологічних підходів до вивчення мов. Автори акцентують увагу на важливості урахування індивідуальних психолого-когнітивних аспектів (сприйняття, запам'ятовування, відтворення) інформації різними категоріями учнів мовних класів.
Keywords: cognitive linguistics; comparative linguistics; educational services; international education; когнітивна лінгвістика; порівняльне мовознавство; освітні послуги; міжнародна освіта